PEDAGOGICAL MECHANISMS OF INTRODUCING INTERACTIVE TECHNOLOGIES TO STUDENTS IN PRACTICAL AND SEMINAR CLASSES - Kadyrova Buzulaykho Turgunovna (Journals Park Publishing, 2023)
This article provides information about the lesson, practical training and its types, as well as pedagogical mechanisms of introducing interactive technologies in practical and seminar training for students.
Keywords: lesson, practical, interactive, solution, student, pedagogical, content, goal, method.